2019
DOI: 10.1021/acs.jpcc.9b07626
|View full text |Cite
|
Sign up to set email alerts
|

Optical Voltammetry of Polymer-Encapsulated Single-Walled Carbon Nanotubes

Abstract: The semiconducting single-walled carbon nanotube (SWCNT), noncovalently wrapped by a polymeric monolayer, is a nanoscale semiconductor-electrolyte interface under investigation for sensing, photonics, and photovoltaic applications. SWCNT complexes are routinely observed to sensitize various electrochemical/redox phenomena, even in the absence of an external field. While the photoluminescence response to gate voltage depends on the redox potential of the nanotube, analogous optical voltammetry of functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Feature importance analysis showed that the intensity ratios contributed most to platform predictions, as compared to wavelength shifts. We believe that this phenomenon may result from the fact that SWCNT intensity exhibits greater sensitivity to more physicochemical phenomena than emission wavelength ( 39 , 42 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feature importance analysis showed that the intensity ratios contributed most to platform predictions, as compared to wavelength shifts. We believe that this phenomenon may result from the fact that SWCNT intensity exhibits greater sensitivity to more physicochemical phenomena than emission wavelength ( 39 , 42 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that SWCNT donor–acceptor properties are strongly affected by the intervening coating and how they mediate the donor–nanotube interaction. Previous models ascribe the effects of SWCNT coating/wrappings to electronic hybridization with the carbon sidewall. ,, One important implication of this hybridization phenomenon is that photosensitized donor–acceptor systems, which depend on how and where donors and acceptors make contact, are susceptible to inefficiencies that arise from controllable variables such as preparation, dispersion, and encapsulation. We used the polymer-nanotube-porphyrin complex as a model nanoscale interface since emission intensity changes have been observed for other aromatic chromophores that directly coat the SWCNT sidewall .…”
Section: Discussionmentioning
confidence: 99%
“…Well-plate photoluminescence-excitation spectroscopy was performed using a SuperK Extreme supercontinuum laser, as previously described . Briefly, a supercontinuum laser source, operated in 3 nm steps from 500 to 839 nm, was fed through fiber optics into a 20× infrared air objective (Olympus LCPLN20XIR) under an inverted microscope (Olympus IX-71).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single walled carbon nanotubes (SWNT) are constituent parts of many new hybrid material systems designed for nanotechnology applications, such as sensing, biological imaging, electronics, and gene delivery [1][2][3][4][5][6][7][8][9][10] . Noncovalent polymer adsorption is a widely used method to functionalize SWNTs, while also solubilizing them in aqueous environments by forming a "corona phase" on the SWNT surface.…”
Section: Introductionmentioning
confidence: 99%